Designing a Chess Game Application Using the Android-Based Breadth First Search Method - Ade, Lestari; Rismayanti, Rismayanti; Dharmawati, Dharmawati (Journal of Computer Science and Informatics Engineering, 2023)
Various efforts have been made to tackle the complexity of problems in chess, known for being challenging due to its classification as NP-complete. A large number of researchers and software developers are actively seeking ways to enhance computer performance in solving this game. One widely discussed approach is the Alpha Beta Pruning algorithm, designed to reduce the number of nodes evaluated in the search for an optimal solution. As an alternative, this research will explore the use of Breadth First Search algorithm to find the best strategies in chess, aiming to increase the challenges faced by users in completing the game